Analisis Kesiapan Implementasi Pajak Karbon di Indonesia - Susanto, Imam; Ulpa, Robi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
This research aims to analyze the government's readiness to implement carbon tax in Indonesia based on Law no. 7 of 2021. This analysis uses variables: Policy standards and targets, resources, characteristics of implementing organizations, communication between organizations, attitudes of implementers, social, economic and political environment. The method used is descriptive qualitative. The sample for this research is an analyst at the Fiscal Policy Agency of the Ministry of Finance of the Republic of Indonesia. The sample was carried out using the purposive sampling method. Data collection techniques use observation, interviews and documentation. Data analysts use the inductive data analysis method, which is a general analysis method carried out by researchers which is based on the results of field research such as interviews, then interpretation is carried out, meaning is sought and conclusions are drawn (verbatim analysis). The research results show that the government's readiness is quite good with the existence of Law no. 7 of 2021 and Presidential Decree no. 98 of 2021, and the Ministry of Finance is currently preparing implementing regulations for this law and is waiting for it to be ratified by the legislature (DPR).